(untitled) (Global Journal of Science Frontier Research, 2023)
The main source of livelihood in Uganda is smallholder farming It is the most common type of agriculture practice supporting more than 70 of the population thus a dire need to devise means to sustain and improve it towards poverty reduction and socio-economic development resulting from the agricultural sector This study investigates the Level and Suitability of ICT Usage for Agricultural Information Dissemination in Rubanda Mayuge Districts and Mbarara City of Uganda The study adopted the survey design of the cross-sectional and used structured questionnaires Data collected were analysed using descriptive statistics of frequency counts and percentages The study recommended that agricultural information dissemina- tion should always be disseminated and reiterated using newer and more complex ICT devices and platforms but the priority and emphasis must be placed on mobile phones and radio being the leading types of ICT used for agricultural information dissemination in Rubanda district Mayuge district and Mbarara city